Three novel umami peptides derived from the alcohol extract of the Pacific oyster (Crassostrea gigas): Identification, characterizations and interactions with T1R1/T1R3 taste receptors - Baifeng Fu; Di Wu; Shuzhen Cheng; Xianbing Xu; Ling Zhang; Lishu Wang; Hesham R. El-Seedi; Hanxiong Liu; Ming Du (Food Science and Human Wellness)
Oyster (Crassostrea gigas), the main ingredient of oyster sauce, has a strong umami taste. In this study, three potential umami peptides, FLNQDEEAR (FR-9), FNKEE (FE-5), and EEFLK (EK-5), were identified and screened from the alcoholic extracts of the oyster using nano-HPLC-MS/MS analysis, iUmami-Scoring Card Method (iUmami-SCM) database and molecular docking (MD). Sensory evaluation and electronic tongue analysis were further used to confirm their tastes. The threshold of the three peptides ranged from 0.38 to 0.55 mg/mL. MD with umami receptors T1R1/T1R3 indicated that the electrostatic interaction and hydrogen bond interaction were the main forces involved. Besides, the Phe592 and Gln853 of T1R3 were the primary docking site for MD and played an important role in umami intensity. Peptides with two Glu residues at the terminus had stronger umami, especially at the C-terminus. These results contribute to the understanding of umami peptides in oysters and the interaction mechanism between umami peptides and umami receptors.